Validation of Dodd's Model for Differential Diagnosis of childhood speech sound disorders: a longitudinal community cohort study. (27th August 2018) - Ttofari Eecen, Kyriaki; Eadie, Patricia; Morgan, Angela T; Reilly, Sheena
Abstract : Aim: Dodd's Model for Differential Diagnosis is one of the available clinical diagnostic classification systems of childhood speech sound disorders. Yet we do not understand the validity of this system beyond clinical samples, precluding its application in epidemiological or population‐based research. This study aimed to determine the prevalence of subgroups of speech sound disorders in a community sample, relative to past clinical samples, in children speaking standard Australian English. Method: We examined speech development in a community‐ascertained sample of children at 4 years ( n =1607). Inclusion for speech sound disorder was a score of less than or equal to 1 standard deviation on a standardized speech test, and/or research assistant concern, and/or three or more speech errors on sounds typically acquired by 4 years. Dodd's model was then applied to 126 children. Results: Data revealed proportions of children across Dodd's diagnostic subgroups as follows: suspected atypical speech motor control (10%); inconsistent phonological disorder (15%); consistent atypical phonological disorder (20%); phonological delay (55%); and articulation disorder alone (0%). The findings are in line with known prevalence of these subgroups in clinical populations. Interpretation: Our findings provide additional support for speech‐language pathologists to use this system in clinical practice for differential diagnosis and targeted intervention of speech sound disorders in children. What this paper adds: Dodd's Model for Differential Diagnosis is the first classification system of speech sound disorders to be applicable to both clinical and community cohorts. What this paper adds: Dodd's Model for Differential Diagnosis is the first classification system of speech sound disorders to be applicable to both clinical and community cohorts. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. This article is commented on by Geytenbeek on page 626 of this issue. Resumen: Aplicación del modelo de Dodd para el diagnóstico diferencial de los trastornos del sonido del habla infantil: un estudio longitudinal de cohorte comunitario: Objetivo: El modelo de Dodd para diagnóstico diferencial es uno de los sistemas de clasificación clínicos disponibles de trastornos del sonido del habla – articulación ‐ infantil. Sin embargo, no comprendemos la validez de este sistema más allá de las muestras clínicas, lo que impide su aplicación epidemiológica o de investigación basada en la población. Este estudio tuvo como objetivo determinar la prevalencia de subgrupos de trastornos del sonido del habla en una muestra de la comunidad, en relación con muestras clínicas pasadas, en niños que hablan inglés australiano estándar. Método: Examinamos el desarrollo del habla en una muestra de niños determinada en la comunidad en 4 años (n = 1607). La inclusión para el trastorno de sonido del habla fue una puntuación menor o igual a 1 desviación estándar en una prueba de habla estandarizada y / o preocupación del asistente de investigación, y / o tres o más errores de habla en sonidos típicamente adquiridos a los 4 años. El modelo de Dodd se aplicó a 126 niños. Resultados: Los datos revelaron proporciones de niños en los subgrupos de diagnóstico de Dodd de la siguiente manera: sospecha de control del habla atípica (10%); trastorno fonológico inconsistente (15%); trastorno fonológico atípico consistente (20%); retraso fonológico (55%); y trastorno articulación aislado (0%). Los hallazgos concuerdan con la prevalencia conocida de estos subgrupos en poblaciones clínicas. Interpretación: Nuestros hallazgos proporcionan apoyo adicional para fonoaudiologos para usar este sistema, en la práctica clínica, para el diagnóstico diferencial y la intervención dirigida de trastornos de sonido del habla en niños. Resumo: Aplicação do Modelo de Dodd para diagnóstico diferencial de desordens da fala em criança: um estudo de coorte longitudinal em uma comunidade: Objetivo: O Modelo de Dodd para Diagnóstico Diferencial é um dos sistemas de classificação disponíveis para diagnóstico clínico de desordens da fala. Ainda não se conhece a validade destes sistema além de amostras clínica, o que limita sua aplicação em pesquisas epidemiológicas ou populacionais. Este estudo visou determinar a prevalência de subgrupos de desordens da fala em uma amostra de uma comunidade, com relação a amostras clínicas anteriores, em crianças falantes de inglês australiano padrão. Método: Examinamos o desenvolvimento da fala em uma amostra de crianças com 4 anos de idade ( n =1607) pertencentes a uma comunidade. A inclusão para desordem da fala foi um escore menor ou igual a 1 desvio padrão em um teste padronizado de fala, e/ou preocupação pelo pesquisador, e/ou três ou mais erros de pronúncia de sons tipicamente adquiridos até a idade de 4 anos. O modelo de Dodd então foi aplicado a 126 crianças. Resultados: Os dados revelaram proporções de crianças entre os subgrupos diagnósticos de Dodd como: suspeita de controle motor da fala atípico (10%); desordem fonológica inconsistente (15%); desordem fonológica consistente atípica (20%); atraso fonológico (55%) e desordem isolada da articulação (0%). Os achados se alinham com a prevalência conhecida destes subgrupos em populações clínicas. Interpretação: Nossos achados fornecem suporte adicional para que fonoaudiólogos usem este sistema na prática clínica para o diagnóstico diferencial e intervenção direcionada de desordens da fala em crianças.